2003
DOI: 10.1152/ajpheart.00520.2003
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate causes a loss in human cerebral endothelial barrier integrity through activation of NMDA receptor

Abstract: l-Glutamate is a major excitatory neurotransmitter that binds ionotropic and metabotropic glutamate receptors. Cerebral endothelial cells from many species have been shown to express several forms of glutamate receptors; however, human cerebral endothelial cells have not been shown to express either the N-methyl-D-aspartate (NMDA) receptor message or protein. This study provides evidence that human cerebral endothelial cells express the message and protein for NMDA receptors. Human cerebral endothelial cell mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(151 citation statements)
references
References 37 publications
13
133
2
3
Order By: Relevance
“…Consistent with these reports, we show in this study that inhibition of the NMDA receptors, which participate in tyrosine hyperphosphorylation of occludin, selectively protect against glutamate-induced disruption of BMEC integrity (Figure 8). These results are supported by earlier observations on the involvement of the NMDA receptors in the regulation of the BBB functions and endothelial permeability (Sharp et al, 2003). However, it should be noted that disruption of tight junctions was also linked to occludin dephosphorylation at the serine/threonine residues (Andreeva et al, 2001;Clarke et al, 2000;Hirase et al, 2001).…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with these reports, we show in this study that inhibition of the NMDA receptors, which participate in tyrosine hyperphosphorylation of occludin, selectively protect against glutamate-induced disruption of BMEC integrity (Figure 8). These results are supported by earlier observations on the involvement of the NMDA receptors in the regulation of the BBB functions and endothelial permeability (Sharp et al, 2003). However, it should be noted that disruption of tight junctions was also linked to occludin dephosphorylation at the serine/threonine residues (Andreeva et al, 2001;Clarke et al, 2000;Hirase et al, 2001).…”
Section: Discussionsupporting
confidence: 84%
“…Our study showed that IgG anti-NR2 glutamate receptor antibody titers in the CSF were significantly positively correlated with IgG anti-NR2 glutamate receptor antibody titers in the serum of patients with SLE. Recently, Sharp et al reported that human cerebral endothelial cells express the message and protein for NMDA receptor subunits NR2a and NR2b (12). That report and results from our study support the possibility that anti-NR2 glutamate receptor antibodies may be produced only outside the CNS and enter the CSF as a result of damage in the blood-brain barrier.…”
Section: Association Of Igg Anti-nr2 Glutamate Receptor Antibodies Insupporting
confidence: 90%
“…This excess NMDA receptor activation is largely responsible for cytotoxic edema of neurons (Sharp et al 2003). Studies have shown that BBB ECs also express both NMDA and metabotropic glutamate receptors (Krizbai et al 1998;Sharp et al 2003).…”
Section: Modulation Of Channels and Transportersmentioning
confidence: 99%